X平方+1/X平方-1 -X-2/X-1 / X-2/X
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 02:18:33
X平方+1/X平方-1-X-2/X-1/X-2/XX平方+1/X平方-1-X-2/X-1/X-2/XX平方+1/X平方-1-X-2/X-1/X-2/X原式=(X^2+1)/{x+1)(x-1)}-(X
X平方+1/X平方-1 -X-2/X-1 / X-2/X
X平方+1/X平方-1 -X-2/X-1 / X-2/X
X平方+1/X平方-1 -X-2/X-1 / X-2/X
原式=(X^2+1)/{x+1)(x-1)} -(X-2)/(X-1) *x /(X-2)
=(X^2+1)/{x+1)(x-1)} -x/(X-1)
={(X^2+1)-x(x+1)}/{(x+1)(X-1)}
=(X^2+1-x^2-x)/{(x+1)(X-1)}
=(1-x)/{(x+1)(X-1)}
=-(x-1)/{(x+1)(X-1)}
=-1/(x+1)
x平方+x+1
(x平方+x)(x平方+x-2)=-1 用换元法
x平方-3[2x-5(x平方-x+1)]
{x平方+x+1}{x平方+x+2}减12
2/x-x的平方-1/x的平方-x
(2x+1)平方-x平方
(x+1)平方-2x
(x平方-1)的平方-(2x+2)平方 (x平方+x)(x平方+x-2)-3(x平方-1)的平方-(2x+2)平方(x平方+x)(x平方+x-2)-3分解因式
(1-x/3-x)平方除以x平方-6x+9/9-x平方*1/x平方-2x+1
请化简:(x的平方-1)(x的平方-x)分之(x的平方+x)(x的平方-2x+1)
x/x平方-x+2=2x/x+1
(-2x平方+3x)-[5x-(2x平方+1)-x平方] 化简
方程2/X平方+X+3/X平方-X=4/X平方-1
2x平方-4x+1=2(x+?)平方+?
化简x平方+x-2分之x平方-1
limx→∞ x平方-1 /2x平方-x
因式分解(x平方-x)平方-(x-1)平方
化简:x平方+x / x-1 除以x平方-1 / x平方-2x+1-(2x-1)是这样的x平方+x / x-1 除以x平方-1 / x平方-2x+1-(2x-1)